Djon África - Miller Guerra, João, 1974-; Pinho, Pedro; Nha Bibinha, Bitori; Cardoso, Isabel; Moreira, Miguel (Actor) (Terratreme, 2018)
A kindhearted and carefree young Rastafarian named Miguel, a.k.a. Djon África - is a Portuguese-born musician of Cape Verdean descent who identifies as African even though he's never been to the continent. He is prompted to go on a search for his father. All he knows is what his grandmother tells him. --